Hands-On Data Analysis with Scala Perform Data Collection, Processing, Manipulation, and Visualization with Scala. - Gupta, Rajesh (Packt Publishing, Limited, 2019)
This book will help you perform effective data analysis with Scala using practical examples. You will come across different challenges and their effective solutions for a variety of data processing tasks - be it data exploration, data manipulation, or real-time data analysis using Apache Spark.